Leveraging media and health communication strategies to overcome the COVID-19 infodemic - Mheidly, Nour; Fares, Jawad (Journal of public health policy, 2020)
The COVID-19 pandemic has caused a complementary infodemic, whereby various outlets and digital media portals shared false information and unsourced recommendations on health. In addition, journals and authors published a mass of academic articles at a speed that suggests a non-existent or a non-rigorous peer review process. Such lapses can promote false information and adoption of health policies based on misleading data. Reliable information is vital for designing and implementing preventive measures and promoting health awareness in the fight against COVID-19. In the age of social media, information travels wide and fast, emphasizing a need for accurate data to be corroborated swiftly and for preventing misleading information from wide dissemination. Here, we discuss the implications of the COVID-19 infodemic and explore practical ways to leverage health communication strategies to overcome it. We propose the “Infodemic Response Checklist” as a comprehensive tool to overcome the challenges posed by the current and any future infodemics.